Adsorption of Lysozyme from Human Whole Saliva by Streptococcus sanguis 903 and Other Oral Microorganisms - Laible, Nancy J. (1982)
Several strains of Streptococcus sanguis, Streptococcus mutans, Streptococcus mitis, Actinomyces viscosus, and Actinomyces naeslundii plus fresh isolates of Streptococcus salivarius were surveyed for their abilities to deplete lysozyme from human-whole-saliva supernatant. Bacteria were incubated in saliva for 60 min at 37°C and then removed by centrifugation, and the recovered supernatant solutions were assayed for lysozyme activity by using whole cells of Micrococcus lysodeikticus as the substrate. Mean lysozyme depletions by bacterial strains varied over a wide (eightfold) range. The greatest mean depletion of lysozyme (60 to 70%) was observed with S. sanguis (biotype I), serotype b of S. mutans, and the fresh S. salivarius isolates. The lowest mean depletion was noted with S. mitis (15%) and biotype II S. sanguis (ca. 30%). The remaining species and strains exhibited an intermediate degree of depletion. In studies with S. sanguis 903, lysozyme was depleted by normal or heated (90°C, 30 min) bacteria and could be recovered from the organism. Furthermore, under appropriate conditions, lysozyme depletion by cells at 0 and 37°C was very similar. On the basis of these observations, we concluded that depletion was due to the adsorption of lysozyme by the organism. With S. sanguis 903, lysozyme adsorption depended on the concentration of bacteria, time of incubation, and the ionic strength of the medium. The extent of adsorption, however, was independent of pH's of 3.9 to 8.3. When a low concentration of S. sanguis 903 was used, lysozyme adsorption reached saturation (4 μg of adsorbed lysozyme per 10(7) cells) at 20 μg of lysozyme added per ml. Salivary lysozyme adsorption by several other oral microorganisms (A. viscosus WVU 626 and WVU 627, S. sanguis 73×11, S. mutans BHT, and S. salivarius NG) was similar to that of S. sanguis 903 in sensitivity to ionic strength. Lysozyme adsorption by S. sanguis 903 from either a buffer solution or a saliva supernatant was more sensitive to ionic strength at 0 than at 37°C. On the basis of results from experiments in saliva versus buffer, we concluded that saliva had no major effect on the extent of lysozyme adsorption by S. sanguis 903 other than providing a source of ionic strength. A comparison of pH and ionic strength effects on lysozyme adsorption by S. sanguis 903 with literature reports of lysozyme lysis of whole cells and hydrolysis of cell walls, peptidoglycan, and (GlcNAc)(4) suggested that adsorption by S. sanguis 903 was more dependent on electrostatic interactions than was lysozyme catalysis. The possibility is discussed that anionic bacterial surface components mediate lysozyme adsorption and temper the potential effects of lysozyme on the microorganisms.